2011
DOI: 10.5539/elt.v4n4p262
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Morphological Awareness and Vocabulary Size of EFL Learners

Abstract: The aim of this study is to investigate the relationship between morphological awareness and vocabulary knowledge of Iranian high school students. Nation's Vocabulary Level Test (VLT) was used to test students' knowledge of words drawn from the 2000, 3000 and 5000 most frequent occurring word families. Two morphological awareness tasks (a morpheme identification task and a morphological structure test) were also used to assess students' morphological awareness. The VLT results reveal that the students performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 18 publications
(22 reference statements)
3
16
0
Order By: Relevance
“…The data illustrated that and there is a no significant difference between the achievement of experimental group and control group regarding morphological structure test. This is in line with the premise posed by Rasinski et al (2008) who claim that exposing students to Greek and Latinate word elements could be an effective vocabulary learning strategy This study also is consistent with Bowers & Kirby (2009), Tabatabaei &Yakhabi (2011), Gilbert, Goodwin, Compton, andKearns (2013), Saeidi & Mirzapour (2013), Goodwin, Gilbert and Cho (2013), and Paiman, Thai & Yuit (2015) studies which reported that learners who have morphological awareness were able to discriminate morphologically structured word from simple words.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The data illustrated that and there is a no significant difference between the achievement of experimental group and control group regarding morphological structure test. This is in line with the premise posed by Rasinski et al (2008) who claim that exposing students to Greek and Latinate word elements could be an effective vocabulary learning strategy This study also is consistent with Bowers & Kirby (2009), Tabatabaei &Yakhabi (2011), Gilbert, Goodwin, Compton, andKearns (2013), Saeidi & Mirzapour (2013), Goodwin, Gilbert and Cho (2013), and Paiman, Thai & Yuit (2015) studies which reported that learners who have morphological awareness were able to discriminate morphologically structured word from simple words.…”
Section: Discussionsupporting
confidence: 91%
“…The researchers concluded that the treatment group made better use of pre-test vocabulary knowledge in learning new vocabulary. Results are discussed in light of the growing debate regarding whether to teach many words in a shallow way or to provide deep, rich instruction about fewer words To determine the relationship between morphological awareness and vocabulary size of EFL learners, Tabatabaei & Yakhabi (2011) collected the data from Iranian high school students who were randomly selected. Nation's Vocabulary Level Test (VLT) was used to test students' knowledge of words drawn from the 2000, 3000 and 5000 most frequent occurring word families.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This was seen in the words of Tom 'the man is sleep on the sofa (sleeping) and he is work at a clothes store as a sales assistant (working)'. The fi ndings are in line with the fi ndings of Tabatabaei (2011); Griva and Anastasiou (2009) who stated that learners perform well and they are able to connect morphological awareness in English.…”
Section: Subcategories Of the Linguistic Competencessupporting
confidence: 86%
“…Understanding the internal structure of words is a key component in being able to learn, store, and use new words in an L2. Compared with the extensive literature available on this subject in child language development (Deacon, Kieffer, & Laroche, 2014;Kieffer & Lesaux, 2012;Kuo & Anderson, 2006;McBride-Chang et al, 2008;Tighe & Schatschneider, 2015), few studies have addressed vocabulary adquisition in SLA contexts (Jeon, 2011;Kieffer & Lesaux, 2008;Koda, 2000;Morin, 2003;Tabatabaei & Yakhabi, 2011;Zhang, 2016;Zhang & Koda, 2012), especially with respect to derivational processes in SSL (Serrano-Dolader et al, 2009). But the use of the findings from this limited literature for pedagogical purposes is not only limited by the sheer number of articles about the subject but, more important, by the methodological diversity of the studies that compose this corpus of studies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In 1995, Carlisle coined the term morphological awareness (MA), defining it as the ability to recognize and manipulate morphemes. Within a second language acquisition (SLA) framework, this ability has been associated with the development of both reading comprehension and a broad lexical repertoire (Jeon, 2011;Kieffer & Lesaux, 2008, 2012Koda, 2000;Morin, 2003;Tabatabaei & Yakhabi, 2011;Zhang, 2016;Zhang & Koda, 2012). However, several studies have shown that even after years of language study and practice, learners have difficulty mastering the morphological structure of words in their second language (L2) 1 (Dal Maso, 2009;Lardiere, 2006;Ramírez, Chen, Geva, & Kiefer, 2010;Ramírez, Chen, Geva, & Luo, 2011;Schmitt & Meara, 1997;Schmitt & Zimmerman, 2002;Whitley, 2004).…”
Section: Introductionmentioning
confidence: 99%